2005
DOI: 10.3168/jds.s0022-0302(05)72909-x
|View full text |Cite
|
Sign up to set email alerts
|

Astringency of Bovine Milk Whey Protein

Abstract: Whey protein solutions at pH 3.5 elicited an astringent taste sensation. The astringency of whey protein isolate (WPI), the process whey protein (PWP) that was prepared by heating WPI at pH 7.0, and the process whey protein prepared at pH 3.5 (aPWP) were adjusted to pH 3.5 and evaluated by 2 sensory analyses (the threshold method and the scalar scoring method) and an instrumental analysis (taste sensor method). The taste-stimulating effects of bovine and porcine gelatin were also evaluated. The threshold value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 10 publications
2
65
0
Order By: Relevance
“…It is hypothesised that another source of mouthdrying could be the milk proteins typically used in ONS formulations. Previous studies have shown whey proteins to cause mouthdrying through precipitation onto the tongue (Sano, Egashira, Kinekawa, & Kitabatake, 2005); alternatively proteolysis of on b-casein can yield c-caseins which are associated with perceived dryness of milks (Harwalkar, Cholette, McKellar, & Emmons, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesised that another source of mouthdrying could be the milk proteins typically used in ONS formulations. Previous studies have shown whey proteins to cause mouthdrying through precipitation onto the tongue (Sano, Egashira, Kinekawa, & Kitabatake, 2005); alternatively proteolysis of on b-casein can yield c-caseins which are associated with perceived dryness of milks (Harwalkar, Cholette, McKellar, & Emmons, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Components other than iron sulfate, intrinsic to ONS, such as the calcium and milk proteins, may contribute to these attributes. In support of this, calcium salts have been shown to exhibit both astringent and metallic taste properties (Lawless, Rapacki, Horne, & Hayes, 2003) and both whey protein precipitation and casein proteolysis products have been associated with mouthdrying (Harwalkar et al, 1993;Sano et al, 2005). Further research into the properties of ONS ingredients may help to elucidate potential causes of the build up of attributes over repeat consumption.…”
Section: Frequency (%)mentioning
confidence: 88%
“…Though whey proteins are soluble over a wide pH range, whey protein beverages are often formulated at low pH for improved beverage clarity and heat stability (Miller, 2007). Acidic whey protein beverages, however, have been shown to be astringent (Beecher, 2006;Sano, Egashira, Kinekawa, & Kitabatake, 2005), which may limit consumer acceptance of these products.…”
Section: Introductionmentioning
confidence: 96%
“…Where caseins may be directed to cheese production, whey proteins possess an important role as structure enhancers in fresh fermented dairy products, such as yoghurt (Johnson & Lucey, 2006). Increasing the proportion of whey proteins in dairy products is, however, not without challenges, as consequences such as increased astringency (Sano, Egashira, Kinekawa, & Kitabatake, 2005;Tomaschunas, Hinrichs, K€ ohn, & Busch-Stockfisch, 2012), altered aggregation behaviour upon heating and acidification (Kücükcetin, 2008), and decreased aroma intensity (Tomaschunas et al, 2012) may occur.…”
Section: Introductionmentioning
confidence: 98%